The Methods of Sex Education in Costa Rica: Sexual Normality, Cold War and Institutionalization (1968-1970) - Jiménez Bolaños, José Daniel (2021)
This article aims to examine the first discussions that took place within the framework of the institutionalization of the National Plan for Sexual Education in Costa Rica, linked to the topic of the necessary methods to implement this subject in the educational curriculum. First, an analysis is made of the national and global context in which these discussions are installed, emphasizing the influence of the Cold War and the sexual revolution of the sixties. Then, the different institutions that were created during the period and that had a central role in the National Plan are detailed, to end with an analysis of the different methods in dispute. Following Foucault, it is concluded that, despite the criticisms to which the method of silence and the prophylactic method were subjected, the idea of sexual normality in the classroom was not contested.